替罗非班联合阿加曲班对比替罗非班治疗急性穿支动脉粥样硬化性脑梗死的效果观察Comparison of the Efficacy between Tirofiban Combined with Argatroban and Tirofiban in the Treatment of Acute Branch Atheromatous Disease - 罗容，侍海存(LUO Rong, SHI Haicun) (Zhongguo cuzhong zazhi)
目的 初步探索替罗非班联合阿加曲班治疗急性穿支动脉粥样硬化性脑梗死（branch atheromatous disease，BAD）的效果。 方法 回顾性纳入2022年1月—2024年5月在盐城市第三人民医院诊治的轻型BAD患者。根据治疗方案，将患者分为替罗非班联合阿加曲班组（双泵组）和替罗非班组。发病7 d内NIHSS评分增加≥2分或肢体功能评分增加≥1分定义为早期神经功能恶化（early neurological deterioration，END），发病3个月mRS评分＜2分定义为预后良好。 结果 共纳入轻型BAD患者83例，其中双泵组31例，替罗非班组52例，两组基线指标比较差异无统计学意义。双泵组发生END的比例低于替罗非班组［6.5%（2/31）vs. 26.9%（14/52），P=0.046］，差异有统计学意义。双泵组预后良好比例高于替罗非班组［96.8%（30/31）vs. 76.9%（40/52），P=0.036］，差异有统计学意义。双泵组有1例患者出现口腔黏膜渗血，所有患者均未发生颅内出血事件。多因素logistic回归分析结果显示，替罗非班联合阿加曲班治疗是BAD患者不发生END和预后良好的独立影响因素（P＜0.05）。 结论 替罗非班联合阿加曲班治疗较替罗非班治疗能够降低轻型BAD患者END的发生率，增加发病3个月预后良好的比例，且不增加颅内出血风险。Abstract: Objective To explore the effect of tirofiban combined with argatroban in the treatment of acute branch atheromatous disease (BAD). Methods Patients with mild BAD treated at the Yancheng Third People’s Hospital from January 2022 to May 2024 were retrospectively included. According to the treatment plan, patients were divided into the tirofiban combined with argatroban group (dual-pump group) and the tirofiban group. Early neurological deterioration (END) was defined as an increase in NIHSS score of≥2 points or an increase in motor function score of≥1 point within 7 days of onset. A good prognosis was defined as a mRS score of＜2 at 3 months after onset. Results A total of 83 patients with mild BAD were included, with 31 patients in the dual-pump group and 52 patients in the tirofiban group. The baseline clinical data between the two groups showed no statistically significant difference. The proportion of END occurrence in the dual-pump group was statistically lower than that in the tirofiban group [6.5% (2/31) vs. 26.9% (14/52), P=0.046]. The proportion of good prognosis patients in the dual-pump group was statistically higher than that in the tirofiban group [96.8% (30/31) vs. 76.9% (40/52), P=0.036]. In the dual-pump group, one patient developed oral mucosal bleeding, while no intracranial hemorrhage events occurred in all patients. Multivariate logistic regression showed that tirofiban combined with argatroban was the treatment of BAD independent influencing factors for non-END and good prognosis (P<0.05). Conclusions The combination of tirofiban and argatroban in treating mild BAD patients can reduce the incidence of END, increase the proportion of patients with good prognosis at 3 months after onset, and does not increase the risk of intracranial hemorrhage.